Serum Parathyroid Hormone Is a New Potential Risk Factor in Multiple Myeloma. (19th May 2014) - Kang, Min-Gu; Won, Eun-Jeong; Choi, Hyun-Woo; Kim, Hye-Ran; Choi, Hyun-Jung; Park, Hye-Ri; Shin, Jong-Hee; Suh, Soon-Pal; Ryang, Dong-Wook; Shin, Myung-Geun
Abstract : We hypothesized that serum PTH might be associated with various clinicopathological parameters in multiple myeloma (MM). So we investigated the implications of serum PTH in MM patients and the relationship with other risk factors of MM. A total of 115 patients who were newly diagnosed with MM were enrolled. Serum PTH level was 24.7 ± 34.9 (ranged 0.0–284.1) pg/mL. Serum levels of IgG, IgM, FLC-lambda, albumin, and LDH were in positive correlation with serum PTH. Compared to non-high PTH (<68.3 pg/mL) group, the hazard ratio (HR) for overall survival was higher for group with high PTH level (≥68.3 pg/mL) (HR, 1.710). Furthermore, the patient group with high PTH level showed inferior progression-free survival than non-high PTH group (P = 0.056 ). Interestingly, subgroup analysis showed that serum PTH level at diagnosis was associated with risk factors and clinical outcome in MM patients, especially in complete remission group, transplantation cases, ISS stage II cases, and cases without chromosome abnormality. In conclusion, this study showed that blood PTH level in MM at diagnosis was associated with risk factors and clinical outcome in MM patients.